Galectin-3 enhances extracellular matrix associations and wound healing in monkey corneal epithelium. (August 2015) - Fujii, Atsuko; Shearer, Thomas R.; Azuma, Mitsuyoshi
Abstract: Poor healing of epithelial wounds in cornea is a major clinical problem, leading to persistent epithelial defects and ulceration. The primary cause is poor cell migration over the wound. Carbohydrate-binding protein galectin-3 binds to extracellular matrixes (ECMs) and promotes lamellipodia formation by cross-linking to α3 integrin. Recombinant galectin-3 also facilitates wound healing in the rodent cornea. The purposes of the present experiments were to: (1) establish epithelial wound healing models in monkey corneal explant culture, the models more relevant to human, (2) evaluate the healing effect of galectin-3 in our models, and (3) determine if galectin-3 enhances cell adhesion by interacting with ECMs on corneal surface and their ligand integrins. Monkey corneas with central wounds produced by sodium hydroxide (NaOH) or n-heptanol were incubated with or without recombinant galectin-3. The defected area was stained with sodium fluorescein. Primary isolated corneal epithelial cells from monkey were cultured with or without galectin-3 on plates coated with ECMs or integrins, and the number of adhering cells was counted. Galectin-3 expression in various eye tissues was visualized by immunoblotting. NaOH caused loss of epithelial cells and basement membrane. n-Heptanol removed epithelial cells, but the basement membrane was retained. These corneal defects spontaneously became smaller in a time-dependent manner. Exogenous galectin-3 enhanced wound healing in both NaOH and n-heptanol models. Galectin-3 also enhanced cell adhesion onto the major ECMs found in the basement and Bowman's membranes and onto integrins. Relatively high levels of galectin-3 were detected in corneal and conjunctival epithelium, but tear fluid contained negligible galactin-3. These results suggested that the enhanced binding of epithelial cells to ECMs and integrins caused by galectin-3 might promote cell migration over wounded corneal surfaces. Since tear fluid contained relatively low levels of galectin-3, exogenous galectin-3 may be a beneficial drug to enhance re-epithelialization in human corneal diseases. Highlights: Monkey corneal wound models with and without basement membrane were produced. Exogenous galectin-3 enhanced re-epithelialization in both models. Galectin-3 promoted cell adhesion onto major ECMs and integrins. Galectin-3 was detected at high levels in the epithelium, but negligible in tears.